THE EFFECTIVENESS OF DIRECTED WRITING TO IMPROVE STUDENTS' ABILITY TO WRITE THE ARABIC PARAGRAPHS AMONG STUDENTS IN THE FIFTH SEMESTER AT MISBAH AL-ULUM MODERN ISLAMIC BOARDING SCHOOL.: فعالية الإنشاء الموجه لترقية قدرة الطلاب على كتابة الفقرة العربية لدى الطلاب في الفصل الخامس بمعهد مصباح العلوم الحديث - Maulana, Rizkie (Institut Agama Islam Negeri Lhokseumawe, 2023)
The title of this research is “The effectiveness of Insya’ Muwajjah in improving students’ ability to write the Arabic paragraph among students in the fifth at the Misbahul Ulum Modern Islamic Boarding School - Lhokseumawe.” The problem of the research is the students’ errors in writing the Arabic paragraph in terms of their formation and composition of the Arabic sentences. Hence, The research aims to determine the effectiveness of directed writing in improving students’ ability to write the Arabic paragraph at the Misbahul Ulum Modern Islamic Boarding School. The research method that the researcher relied on in this research is an experimental method and the method of collecting data is by using pre-test and post-test. The results of the research are that the directed writing teaching in teaching the Arabic paragraph writing at the Misbahul Ulum Modern Islamic Boarding School is effective in improving students’ ability to write Arabic paragraphs, the pre-test is 59.00 with a standard deviation of 11. 53. The result of the post-test was 79.00, with a standard deviation of 8.56.